Belewenis van moeders van jong hiperaktiewe kinders - A. J. Cilliers; M. Greeff; M. Poggenpoel (AOSIS, 1993)
An exploratory contextual study was undertaken to expand the insight into and the meaning of the perceptions of the mother of a hyperactive child. The phenomenological method of interviewing was used to gather data. The interviews were recorded on tape and later transcribed verbatim. The random test population consisted of eight participants who you're specially selected for the purpose of this study. Data was analysed by way of content analysis. The results firstly crystallised in the mother's experiences with her hyperactive child and secondly in the elements which influenced these experiences. The mothers experience is contained in her involvement with her child and in her interaction with Mm. She experiences vehement feelings of anger, empathy, insufficiency, guilt and depression. At the same time there is the perception that she is responsible for her child's hyperactivity and the accompanying behavioural problems. The mother finds herself in a stressful situation where she is a buffet between her child and the world. Her experience is influenced inter alia by her religious system, personal stress, the behaviour of the hyperactive child, and the availability of support systems.